Role of apolipoprotein E in the lipolytic conversion of beta-very low density lipoproteins to low density lipoproteins in type III hyperlipoproteinemia. - Ehnholm, C (1984)
The beta-very low density lipoproteins (beta-VLDL) that accumulate in type III hyperlipoproteinemic subjects can be divided into two fractions (fraction I and fraction II), which differ in size, lipid composition, and the type of apolipoprotein B (apo-B) present in the particles. The apo-B48-containing particles (fraction I) are of intestinal origin, while apo-B100-containing particles (fraction II) are derived from the liver. Both fractions contain a defective form of apo-E referred to as apo-E2. Intravenous infusion of heparin into two subjects with type III hyperlipoproteinemia resulted in the complete removal of fraction II particles from density less than 1.006 g/ml, while fraction I particles remained at this density. In vitro studies confirmed that fraction I particles did not change density when subjected to hydrolysis with lipoprotein lipase, while fraction II particles shifted to the intermediate density lipoprotein range (approximately equal to 1.02 g/ml). When the beta-VLDL were hydrolyzed by lipoprotein lipase in the presence of density greater than 1.21 g/ml lipoprotein-deficient plasma, the addition of normal apo-E (apo-E3), but not apo-E2, resulted in a shift of fraction II particles to the low density lipoprotein (LDL) range (approximately equal to 1.05 g/ml). Fraction I particles did not undergo a shift to this higher density, supporting previous observations that apo-B48-containing particles are not converted to LDL. The demonstration that apo-B100-containing particles in type III hyperlipoproteinemic subjects could be converted to particles with the density of LDL suggests that apo-E plays a role in the normal conversion of VLDL to LDL. The mutant form of apo-E (apo-E2) found in the beta-VLDL from type III hyperlipoproteinemic subjects appears to impede this conversion, whereas the addition of normal apo-E (apo-E3) allows the processing to occur.